Inequality, Globalization, and Leadership - Hicks, Douglas A. (The annual of the Society of Christian Ethics, 2001)
Economists and sociologists have shown that social norms and relative standing are significant factors in the perception of one's well-being. Globalization increasingly extends the scope of the